Media literacy education: strategies and challenges - Iryna K. Pokulyta; Olha V. Sotska (CTE Workshop Proceedings)
In the era of the information society, the abundance of information that we are exposed to is overwhelming. The quality, verifiability, and motivational orientation of this information vary widely, making it difficult to discern what is true and what is not. This is especially true in the context of the pandemic, where social isolation has made us more reliant on digital media for information. As a result, creating conditions for information security has become a primary task. One approach to solving this problem is media literacy education. Media literacy education is the process of teaching people how to critically analyze and evaluate media messages, as well as how to create their own media messages. It is an essential skill in today’s world, where we are constantly bombarded with information from a variety of sources. This article discusses strategies for introducing media education in international organizations. It analyzes the specifics of media education and media literacy in various aspects and examines the role of critical thinking in countering information aggression. Critical thinking is an essential tool for evaluating the quality and verifiability of information, and it is particularly important in countering the risks and dangers associated with establishing norms of social distance for the prevention of epidemiological threats.